Physical Fitness and Dietary Intake Improve Mental Health in Chinese Adolescence Aged 12–13 - Liang, Wenjie; Fu, Jian; Tian, Xin; Tian, Jiaxue; Yang, Yu; Fan, Wencui; Du, Zijuan; Jin, Zheyu (Frontiers in Integrative Neuroscience, 2022)
Background Mental health has become a major public health issue worldwide. Biological and epidemiological studies have suggested that diet and physical fitness play a role in the prevention or cure of mental disorders. However, further research is required to elucidate the relationship between diet, physical fitness, and mental health. The study aims to provide a theoretical basis for promoting an adolescent healthy lifestyle and preventing mental problems by exploring the relationship between physical fitness, calcium intake, calorie intake, and adolescent mental health. Methods A cross-sectional study of a sample of adolescents (N = 253, 12–13 years) was conducted. The study involved adolescents from three middle schools in Central Jiangsu Province, including 136 boys and 117 girls. Weight, height, and body mass index were measured. Physical fitness was scored using the Chinese National Student Physical Fitness Standard. Diet data were collected using a weighed 7-day food diary to estimate energy intake and dietary calcium intake. The mental health status of the participants was assessed using the Chinese Middle School Student Mental Health Scale. A T-test and analysis of variance were used to analyze the differences of variables between different genders and body mass index, and Pearson correlation and stepwise multiple regression were used to explore the relationship between physical fitness, dietary intake, and mental health. Results The height (165.13 ± 8.07), weight (55.24 ± 13.00), and strength quality (64.93 ± 21.66) of boys are higher than those of girls (161.67 ± 6.44,48.99 ± 8.97, 58.40 ± 23.75, P < 0.05), and the flexibility quality (74.59 ± 14.75) of girls is higher than that of boys (68.30 ± 20.84) (P < 0.05). There were significant differences in the total scores of speed and physical fitness (F values were 4.02187.73, 3.07, 5.95, 10.33, and 9.52, respectively, P < 0.05). There was a significant positive correlation between calcium intake, cardiopulmonary fitness, and mental health (r = 0.276, P < 0.01; r = 0.159, P < 0.05). Calcium intake and cardiopulmonary fitness could explain 8.4% of the changes in the mental health of adolescents aged 12–13(ΔR2 = 0.084, P < 0.05). Conclusion Adequate calcium intake and the improvement of cardiopulmonary fitness in adolescents aged 12–13 are essential for the good development of their mental health. Future research in this field should examine the prospective associations between multiple measures of physical fitness composition and other nutrients ingested and mental health outcomes, as well as intervention studies that seek to provide evidence of causality.